Functionality Requirements for Fleet Management System - Mohd. Razalan, Kamal (2005)
The project aims to identify the functional requirements of fleet management system with Unified Modelling Language (UML). Three main phases were involved in this project, which are defining requirements, analyze requirements and validate functionalities. The functionalities of requirement are presented by using UML diagrams that consists of use case diagram, use case specification, sequence diagram, collaboration diagram and class diagram. The prototype was built to provide a guideline in developing the running system of Fleet Management System on user’s needs.